Gain enhancement of a wideband rectangular ring monopole millimeter‐wave antenna using artificial magnetic conductor structure. Issue 10 (16th July 2022) - Kumar, Ashok; Kumar, Ashok; Kumar, Arjun
Abstract: In this article, the design and development of an artificial magnetic conductor (AMC)‐backed compact wideband rectangular ring monopole antenna with high gain is proposed for millimeter‐wave (mmWave) applications. It is constructed through stacking a coplanar waveguide (CPW)‐fed rectangular ring patch monopole antenna over a square modified AMC reflector surface of 5 × 5 periodic unit cells. Primarily, the ring monopole antenna of size 1.21 λ 0 × 1.21 λ 0 × 0.023 λ 0 (at 28 GHz) is designed and exhibits wide impedance bandwidth of 30.64% (25.98–35.38 GHz, 9.4 GHz), a peak gain of 4.86 dBi and front‐to‐back ratio (FBR) up to 5.2 dB. To enhance the radiation performance of the monopole antenna, a periodic lattice of 5 × 5 unit cells modified square AMC surface with a gap of 0.84 λ 0 is proposed and it functioned as reflector which enhances the peak gain of about 77% and it contributes FBR up to 15 dB. Measured results of the modified square AMC‐backed monopole antenna reveal a wide impedance bandwidth of 31.27% (25.90–35.50 GHz, 9.6 GHz), a peak gain of 8.59 dBi, and stable radiation characteristics.